THE IMPACT OF INTEREST RATE AND FOREIGN EXCHANGE CHANGES ON PUBLIC DEBT IN IRAQ - Lect. Dr. Jabbar Saadoon Darag (American Journals, 2024)
The study analyzed the reciprocal relationship between changes in interest and foreign exchange rates and public debt in Iraq during the period from 2004 to 2023. The research included the concept of public debt, the interest rate and the factors affecting it, the concept of the exchange rate and the factors affecting it, as well as the concept and importance of public debt.Data were used from the Central Bank of Iraq for the period (2004-2023). The study found that there was a relationship between the independent variables represented by the interest rate and the exchange rate on public debt in the short term and the long term. The cointegration program was used, and an autoregressive study of distributed time gaps using ARDL test.
Keywords: Publicc debt, exchange rate, inflation, ARDL.